Adjustment Effects of Maximum Intensity Tolerance During Whole-Body Electromyostimulation Training - Berger, Joshua; Becker, Stephan; Backfisch, Marco; Eifler, Christoph; Kemmler, Wolfgang; Fröhlich, Michael (Frontiers in Physiology, 2019)
Intensity regulation during whole-body electromyostimulation (WB-EMS) training is mostly controlled by subjective scales such as CR-10 Borg scale. To determine objective training intensities derived from a maximum as it is used in conventional strength training using the one-repetition-maximum (1-RM), a comparable maximum in WB-EMS is necessary. Therefore, the aim of this study was to examine, if there is an individual maximum current tolerance plateau after multiple consecutive EMS application sessions. A total of 52 subjects (24.1 ± 3.2 years; 76.8 ± 11.1 kg; 1.77 ± 0.9 m) participated in the longitudinal, observational study (38 male, 14 female). Each participant carried out four consecutive maximal EMS applications (T1-T4) separated by one week. All muscle groups were stimulated successively until their individual maximum and combined to a whole-body stimulation index to carry out a possible statement for the development of the maximum current tolerance of the whole body. There was a significant main effect between the measurement times for all participants (p < 0.001; 𝜂2 = 0.39) as well as gender specific for male (p = 0.001; 𝜂2 = 0.18) and female (p < 0.001; 𝜂2 = 0.57). There were no interaction effects of gender*measurement time (p = 0.394). The maximum current tolerance increased significantly from T1 to T2 (p = 0.001) and T2 to T3 (p < 0.001). There was no significant difference between T3 and T4 (p = 1.0). These results indicate that there is an adjustment of the individual maximum current tolerance to a WB-EMS training after three consecutive tests. Therefore, there is a need of several habituation units comparable to the identification of the individual 1-RM in conventional strength training. Further research should focus on an objective intensity specific regulation of the WB-EMS based on the individual maximum current tolerance to characterize different training areas and therefore generate specific adaptations to a WB-EMS training compared to conventional strength training methods.